OPTIMIZATION OF EMPOWERMENT AND DEVELOPMENT OF VILLAGE ECONOMIC POTENTIAL THROUGH VILLAGE OWNED BUSINESS Entities (BUMDES) (Panggungharjo Kapanewon Sewon, Guwosari Kapanewon Pajangan Village, and Tamantirto Kapanewon Kasihan Village in Bantul Regency) - Sugianto Amran (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
BUMDes is a legal entity established by the village and/or together with the villages for the greatest welfare of the village community. The type of this research is qualitative research. The purpose of this study was to analyze the role and model of Village Owned Enterprises (BUMDes) in empowering and developing economic potential (Panggungharjo Kapanewon Sewon Village, Guwosari Kapanewon Pajangan Village, and Tamantirto Kapanewon Kasihan Village in Bantul Regency). The results of the research show that the role of BUMDes in Panggungharjo Kapanewon Sewon Village, Guwosari Kapanewon Pajangan Village, and Tamantirto Kapanewon Kasihan Village is very important in increasing public awareness that the importance of maintaining a clean village environment, increasing individual ability to change in terms of improving village fund management, opening access to the management of village potentials and create solidarity, namely in the form of a prosperous community helping those who are not yet prosperous. While the empowerment model is divided into two things, namely the first, the way of strategy and the basis of the strategy. Keywords: Village Owned Enterprises (BUMDes), Community Empowerment, Community Development.